2015
DOI: 10.1007/s10753-015-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen Attenuates Lung Injury in Experimental Model of Carrageenan-Induced Pleurisy in Rats

Abstract: The study evaluates the role of Ebselen (Eb), an organoselenium compound in animal model of acute lung injury induced by carrageenan (CG). Wistar rats received saline or 2 % λ-carrageenan in the pleural cavity, and treatment with Eb (50 mg/kg intragastrically) or dexamethasone (Dx) (0.5 mg/kg intraperitoneal) after CG administration. After 4 h, rats were euthanized and the pleural exudate removed for analysis of the total cell count, total protein, lactate dehydrogenase, and nitrite/nitrate. Moreover, lung tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A number of studies have demonstrated the inhibitory actions of orally administered ebselen on lung inflammation in vivo. Experimental models in animals include pulmonary inflammation induced by carrageenin, sephadex, ozone, cigarette smoke and endotoxin [54][55][56][57]. In LPS-induced lung inflammation, ebselen inhibited leukocyte infiltration in association with lowered expression of ICAM-1 adhesion molecule and the inflammatory cytokines, TNFα and IL1β, in lung tissue [55].…”
Section: Ebselen and Lung Inflammationmentioning
confidence: 99%
“…A number of studies have demonstrated the inhibitory actions of orally administered ebselen on lung inflammation in vivo. Experimental models in animals include pulmonary inflammation induced by carrageenin, sephadex, ozone, cigarette smoke and endotoxin [54][55][56][57]. In LPS-induced lung inflammation, ebselen inhibited leukocyte infiltration in association with lowered expression of ICAM-1 adhesion molecule and the inflammatory cytokines, TNFα and IL1β, in lung tissue [55].…”
Section: Ebselen and Lung Inflammationmentioning
confidence: 99%
“…Selenium, a GPx cofactor, activates GPx in vivo and attenuates lipid peroxidation and lung injury early after paraquat intoxication in rats, but did not affect the survival [152]. Ebselen, an organoselenium compound, mimics GPx activity and showed protective action in animal model of pleurisy [153]. BXT-51072 and BXT-51077, seleniumcontaining GPx mimics, prevented TNF-and neutrophil-induced endothelial alterations through the downregulation of endothelial proinflammatory responses [154].…”
Section: Glutathione and Related Enzymesmentioning
confidence: 99%
“…The increase in the vascular permeability is characterized by exudation and it is considered as a major feature of acute inflammation in the inflammatory sites . There is evidence that MPO activity is an indirect marker of active neutrophils (representing 65% of leukocytes) and results in the exudation and migration of monomorphonuclear cells .…”
Section: Discussionmentioning
confidence: 99%